2015
DOI: 10.1155/2015/359315
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Promotes NO Synthesis by Upregulating GCHI Expression under Oxidative Stress Conditions in Sheep Monocytes/Macrophages

Abstract: Many groups of Gram-negative bacteria cause diseases that are harmful to sheep. Toll-like receptor 4 (TLR4), which is critical for detecting Gram-negative bacteria by the innate immune system, is activated by lipopolysaccharide (LPS) to initiate inflammatory responses and oxidative stress. Oxidation intermediates are essential activators of oxidative stress, as low levels of free radicals form a stressful oxidative environment that can clear invading pathogens. NO is an oxidation intermediate and its generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…Importantly, GTPCH1 expression is known to be increased in endothelial cells by enhanced NF-κB activity, a main target activated by TRAF-6 signaling3335. This pathway linking TLR-4 activation with enhanced GTPCH1 expression has been recently fully described in macrophages34. While this mechanism remains mainly speculative until further investigation, these data are in excellent agreement with the hypothesis of EDA as a modulator of eNOS coupling in diabetic aorta via TLR-4.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Importantly, GTPCH1 expression is known to be increased in endothelial cells by enhanced NF-κB activity, a main target activated by TRAF-6 signaling3335. This pathway linking TLR-4 activation with enhanced GTPCH1 expression has been recently fully described in macrophages34. While this mechanism remains mainly speculative until further investigation, these data are in excellent agreement with the hypothesis of EDA as a modulator of eNOS coupling in diabetic aorta via TLR-4.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, this finding was associated with the upregulation of GTPCH1 expression, the main enzyme involved in the synthesis of the NOS coupling factor BH 4 (Fig. 5e and f), known to be increased after TLR-4-triggered NF-κB activity3435. However, no differences in both TRAF-6 and GTPCH1 expression levels were detected in STZ + EDA −/− compared to wild type (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Amplified oxidative stress might decrease HDAC2 further as oxidative stress such as H 2 O 2 and cigarette smoke conditioned media are reported to decrease HDAC2 protein expression via protein modifications, such as phosphorylation, ubiquitination and nitration [11] , [38] , [39] . Notably, viral or bacterial infection or LPS exposure are reported to induce oxidative stress in cells [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that the immunocytes of TLR4-overexpressing transgenic sheep could trigger a more intense immune response to LPS stimulation, including the secretion of various interleukins, rapid neutrophil infiltration, and enhanced oxidative stress 31 - 33 . In our current study, we further surveyed whether the immunocytes of transgenic sheep influence bacterial internalization.…”
Section: Introductionmentioning
confidence: 99%